Cambridge Step Up To IELTS Vol. 1 - Jakeman, Vanessa and McDowell, Clare (Lahore Frontier Publishing, 2002)
This collection of practice tests contains four authentic IELTS papers from Cambridge ESOL, providing excellent exam practice.
Keywords: English language -- International English Language Testing System -- English language--Study and teaching--Foreign speakers -- English language--Examinations